Development of Inventory Management Information System in A Retail Company - Purwasih, Ratih; Mittra Candana, Dori (Jurnal Sains Informatika Terapan, 2024)
The challenge of maintaining accurate and efficient inventory management is a significant issue faced by retail companies. Ineffective inventory management can lead to stockouts, overstocking, and increased operational costs. The objective of this research is to develop an Inventory Management Information System (IMIS) to address these issues by streamlining inventory tracking, minimizing manual errors, and providing real-time data for better decision-making.This study employs a system development methodology that includes requirement analysis, system design, implementation, and evaluation. The IMIS is developed using PHP and MySQL for backend processes, ensuring the system is robust and scalable. Key functionalities of the system include automated inventory updates, low stock alerts, and comprehensive reporting tools.The results of this research indicate that the implementation of the IMIS significantly enhances the accuracy and efficiency of inventory management. The system provides real-time visibility into stock levels, which enables timely restocking and reduces instances of stockouts and overstocking. User feedback highlights high satisfaction with the system's ease of use and its positive impact on operational workflows.In conclusion, the developed IMIS proves to be a valuable tool for retail companies, improving inventory management practices and contributing to more informed strategic decisions through detailed data analysis. This research underscores the importance of integrating information technology solutions in retail operations to enhance efficiency and effectiveness.